2011
DOI: 10.1258/ar.2011.100347
|View full text |Cite
|
Sign up to set email alerts
|

Double reading of radiological examinations in Norway

Abstract: Double reading is common in Norway, especially in residency training, mammography, and PET/PET-CT. It is less common at private centers. Established routines for double reading are scarce. Many institutional heads want more double reading. The potential of double reading to assure quality in radiology should be better exploited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…6 As shown in previous studies, enlarged enhancing lesions on conventional MR images may actually represent pseudoprogression in up to 46.8%-64% of cases. 7,8 The Response Assessment in NeuroOncology (RANO) Working Group 9 proposed that within the first 12 weeks of completion of radiation therapy, when pseudoprogression is most prevalent, tumor progression can only be determined if most of the new enhancement is outside the radiation field or if there is pathologic confirmation of progressive disease.…”
mentioning
confidence: 99%
“…6 As shown in previous studies, enlarged enhancing lesions on conventional MR images may actually represent pseudoprogression in up to 46.8%-64% of cases. 7,8 The Response Assessment in NeuroOncology (RANO) Working Group 9 proposed that within the first 12 weeks of completion of radiation therapy, when pseudoprogression is most prevalent, tumor progression can only be determined if most of the new enhancement is outside the radiation field or if there is pathologic confirmation of progressive disease.…”
mentioning
confidence: 99%
“…Double reading is most common in PET/CT and mammography. In this study they stressed on the importance of double reading to assure quality in radiology 15 .…”
Section: Double Readingmentioning
confidence: 99%
“…During continued follow-up, if lesion stabilizes or shrinks, the initial growth is confirmed pseudoprogression [3]. Previous studies also suggested that enlarged and enhanced lesions on MR images may represent pseudoprogression in 46.8-64% of the cases [4]. Much effort has been taken to distinguish the progression from pseudoprogression through advanced MR imaging techniques, such as DWI and dynamic susceptibility contrast PWI.…”
Section: Introductionmentioning
confidence: 99%